2015
DOI: 10.1016/j.cj.2014.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetic analysis of phosphomannomutase genes in Triticum monococcum

Abstract: In higher plants, phosphomannomutase (PMM) is essential for synthesizing the antioxidant ascorbic acid through the Smirnoff-Wheeler pathway. Previously, we characterized six PMM genes (TaPMM-A1, A2, B1, B2, D1 and D2) in common wheat (Triticum aestivum, AABBDD).Here, we report a molecular genetic analysis of PMM genes in Triticum monococcum (A m A m ), a diploid wheat species whose A m genome is closely related to the A genome of common wheat. Two distinct PMM genes, TmPMM-1 and TmPMM-2, were found in T. monoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…A PCR mix (0.02 cm 3 ) was done by the 2× TB Green Premix Ex Taq II (TaKaRa, Dalian, China) user manual. Thermoamplification was performed in a 96-well plate (Applied Biosystems, Carlsbad, USA) following our previous procedure (Yu et al 2015). Using actin as an internal control, expression of a target gene was compared to an internal gene (Chen et al 2018).…”
Section: Methodsmentioning
confidence: 99%
“…A PCR mix (0.02 cm 3 ) was done by the 2× TB Green Premix Ex Taq II (TaKaRa, Dalian, China) user manual. Thermoamplification was performed in a 96-well plate (Applied Biosystems, Carlsbad, USA) following our previous procedure (Yu et al 2015). Using actin as an internal control, expression of a target gene was compared to an internal gene (Chen et al 2018).…”
Section: Methodsmentioning
confidence: 99%
“…The role of PMM is to catalyze the interconversion between mannose-6-phosphate (M6P) and mannose-1-phosphate (M1P), which are both key precursors of alginate synthesizing (Fig. 5) (May et al 1991;Yu et al 2015). Zielinski et al (1992) has reported that the maximum activation to algC expression was achieved at 0.3 M NaCl, and a higher concentration of NaCl would result in decreased activation.…”
Section: Effects Of Salinity On Alginate-like Exopolysaccharides Algi...mentioning
confidence: 99%